2004
DOI: 10.3200/aeoh.59.3.116-120
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Effects from Work-Related Exposure to Welding Fumes in Hamadan, Iran

Abstract: The authors studied respiratory symptoms and lung function among welders at welding workshops, and among nonwelders, in Hamadan, Iran. They used a questionnaire to record demographic data, smoking habits, and respiratory symptoms. The authors measured pulmonary functions with subjects standing upright. They collected metal fume samples from the respiratory zone of workers and analyzed the samples by atomic absorption spectroscopy. The concentrations of iron and manganese were higher than threshold limit values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…The association between welding exposure duration and decreased pulmonary function were in agreement with other investigation [5], [15]. Previous studies on welders also suggest a cumulative relation between the effects of smoking and welding, hence causing increase respiratory symptom and lung disease [8], [9], [11]. In this study, a comparison was made between pulmonary function parameters of welders and control groups.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…The association between welding exposure duration and decreased pulmonary function were in agreement with other investigation [5], [15]. Previous studies on welders also suggest a cumulative relation between the effects of smoking and welding, hence causing increase respiratory symptom and lung disease [8], [9], [11]. In this study, a comparison was made between pulmonary function parameters of welders and control groups.…”
Section: Methodssupporting
confidence: 91%
“…Reference [10] studied on shipyard welders and caulker-burners and concluded that FEV 1 of smoking welder decrease three times greater than non smoking control. Reference [8], [9], [11] suggest that there is a synergistic relation between the effects of smoking and welding causing lung disease and increased respiratory symptom.…”
Section: Related Researchesmentioning
confidence: 99%
“…28 Few epidemiologic studies have been published analyzing the association between welding and asthma. Two cross-sectional studies 29,30 have shown conflicting results. The study from the United States did not find any association, 29 whereas in the study from Iran, 30 the prevalence of asthma was higher in welders than in nonwelders.…”
Section: Discussionmentioning
confidence: 94%
“…Although the greatest emphasis has been placed on these severe and irreversible neurological disorders, it is important to point out that persistent exposure to high levels of Mn can also provoke a variety of other noxious conditions that result in considerable impairment of normal function and performance in a variety of organs. For example, chronic exposure to Mn can lead to increased susceptibility toward developing pulmonary infections including pneumonia and bronchitis (Baader 1932;Davies and Harding 1949;Rodier 1955;Maigetter et al 1976;Bencko and Cikrt 1984;Roels et al 1987;Saric 1992;Saric and Piasek 2000;Jafari and Assari 2004;Bowler et al 2007;Antonini et al 2009). Similarly, hearing deficits have also been reported in occupations in which individuals are exposed to chronic high levels of Mn (Nikolov 1974;Khalkova and Kostadinova 1986;Korczynski 2000;Josephs et al 2005;Park et al 2006;Da Silva et al 2007;Vezér et al 2007;Bouchard et al 2008).…”
Section: Introductionmentioning
confidence: 98%